Insights on mapping Industry 4.0 and Education 4.0 - Chakraborty, Sourojeet; Gonzalez-Triana, Yris; Mendoza, Jorge; Galatro, Daniela (Frontiers in Education, 2023)
The fourth industrial revolution, or Industry 4.0 (I.D. 4.0), has radically empowered professionals to revamp skills and technologies, to match ever-evolving industry demands. Education 4.0 (E.D. 4.0) is an integral education framework, strategically designed to align with I.D. 4.0 needs. The present work presents high-level insights on mapping I.D. 4.0 to E.D. 4.0, by successfully analyzing the four key existing components of E.D. 4.0, namely, learning methods, competencies, infrastructure and information and communication technologies (ICT). Research questions are formulated along themes aiming to standardize the E.D. 4.0 framework and identify effectiveness and implementation challenges. These posed questions are addressed by performing an exhaustive bibliometric analysis on the associated literature, by clustering relevant publications by field, year, and geography. Our results demonstrate a lack of any currently existent, standardized, and universally accepted framework for mapping I.D. 4.0 to E.D. 4.0, despite trends showing a sharp rise towards incorporating E.D. 4.0 initiatives recently into university curricula. Our analysis procedure can serve as a protocol to define E.D. 4.0 in a more specific context, in an ever-changing global workspace. While unbalanced implementation attempts on how extensively E.D. 4.0 components have been defined and adopted (including discrepancies in implementation policies among countries, and across disciplines), further rigorous assessments are needed to critically assess the necessary requirements and effectiveness, for standardization and implementation a global mapping framework.